Boosting Employee Performance : Compensation and Motivation - Susan Ridwan; Jusdijachlan Jusdijachlan (Dinasti Publisher, 2023)
Many companies believe that income, salary or wages are the main factors that influence employee performance apart from bonuses, incentives, health benefits, holiday allowances, meal allowances, leave allowances and so on. Apart from providing compensation to employees, employee performance is also influenced by work motivation. The method used in this research is to use a descriptive and verification method approach. Data collection techniques were obtained from primary data through interviews, observations and questionnaires. Meanwhile, secondary data was obtained from library data, document review and data acquisition from Bapusipda. For statistical analysis, use correlation coefficient analysis, path analysis, coefficient of determination and hypothesis testing. To make analysis easier, use the software application system 16.0 for Windows. Based on the research results, it is known that Compensation got an average score of 3.20 in the quite good category, Work Motivation got an average score of 3.20 in the quite good category and performance got an average score of 3.26 in the quite good category. Meanwhile, the correlation between Compensation and Work Motivation obtained a close relationship of 0.790. The direct and indirect influence of compensation on employee performance is 0.391 and the direct and indirect influence of work motivation is 0.210. So the total effect is 0.601. Based on the calculation results, the coefficient of determination received a score of 60.1% and the remaining 39.9%, namely other variables that influence employee performance (Case Study at PT. Tiara Payung Putra, Tangerang Regency.